2004
DOI: 10.1007/s10350-003-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

The Rectogenital Septum: Morphology, Function, and Clinical Relevance

Abstract: Because of a coinnervation of the rectal muscle layers and the adjacent longitudinal muscle fibers of the septum, a functional correlation between the two structures during defecation is postulated. On the basis of these findings, a safer dissection of the anterior rectal wall during rectal resection is postulated, thus limiting functional disturbance and preventing neural damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 32 publications
3
63
2
4
Order By: Relevance
“…28 Aigner et al also suggested that fasciae in the pelvis are formed by condensation of loose mesenchyme. 29 We fully agree with both descriptions and believe this has played a major role in the various interpretations of fasciae and nerves surrounding the rectum.…”
Section: Discussionsupporting
confidence: 81%
“…28 Aigner et al also suggested that fasciae in the pelvis are formed by condensation of loose mesenchyme. 29 We fully agree with both descriptions and believe this has played a major role in the various interpretations of fasciae and nerves surrounding the rectum.…”
Section: Discussionsupporting
confidence: 81%
“…Experimental studies have shown that nerve ¢bers and receptors responsible for detecting rectal distension lie in the pelvic fascia and submucosal wall of the distal rectum [Scharli and Kiesewetter, 1970;Lane and Parks, 1977] with nerve ¢bers spreading throughout the rectovaginal wall [Aigner et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…The septum is clearly marked by the visceral pelvic fascia or Denonvilliers fascia that separates the extraperitoneal rectum anteriorly from the vagina (Figs. 3.24 and 3.25 ) or prostate and seminal vesicles [ 8 ]. Developing the plane anterior to the fascia propria or extramesorectal plane may lead to resection of Denonvilliers fascia and is associated with an increased risk of bladder and sexual dysfunction due to sacrifi ce of branches of the pelvic plexus of the hypogastric nerves.…”
Section: Posterior and Lateral Compartmentsmentioning
confidence: 98%